Antenatal voluntary counseling and testing for HIV in Barbados: success and barriers to implementation Asesoramiento y prueba detectora de VIH de carácter voluntario en el período prenatal en Barbados: resultados y barreras al cumplimiento - Alok Kumar; Elizabeth Rocheste; Michelle Gibson; Taniya Gibson; Heather Robinson; Sheila Forde (Pan American Health Organization, 2004)
OBJECTIVE: To determine the success of voluntary counseling and testing (VCT) for HIV and to identify the barriers to implementation when VCT is offered as a package integrated with antenatal care. METHODS: In this descriptive study we investigated antenatal VCT and HIV testing in all post-parturient women at the Queen Elizabeth Hospital, Bridgetown, Barbados, who gave birth between April and September 2002. Data were collected retrospectively from the antenatal care record and by recall during one-on-one interview. RESULTS: Of 1 342 women surveyed, 954 (71.1%) received antenatal counseling and were offered an HIV test. Of the 954 women offered HIV test after counseling, 914 (95.8%) agreed to have the test. Among the women surveyed, 1 106 (82.4%) had a documented HIV test, 914 (85.7%) were tested after documented pretest counseling, and another 192 (14.3%) were tested without documented pretest counseling. Overall, 822 of the 1 342 women surveyed (61.2%) had a documented HIV test result in their antenatal case record at the time of delivery. Of the 1 106 women who had a documented HIV test, the test results were unavailable at the time of delivery in only 284 (21.2%). Among the reasons for unavailability of a documented HIV test result, the most common (45.0%) was that no test was done, followed by unclear documentation of the result. CONCLUSIONS: Twenty-nine percent of surveyed women failed to receive antenatal VCT and this is a cause of concern, for both the high coverage and good quality counseling are key to the overall success and cost effectiveness of the VCT program. Fourteen percent of the women surveyed who did not receive VCT were tested for HIV, a situation that is undesirable because some women may be tested without understanding the full implication of this policy, and as a result the overall impact of VCT may be reduced. OBJETIVO: Determinar los resultados del asesoramiento y de la prueba detectora de infección por VIH aceptados voluntariamente (APV) e identificar las barreras que impiden llevar el ...